BCG vaccination in the first year of life protects children of Indian subcontinent ethnic origin against tuberculosis in England. Issue 1 (March 1991) - Rodrigues, L C; Noel Gill, O; Smith, P G
Abstract : STUDY OBJECTIVE--The aim was to assess the protection conferred by BCG given during the first year of life against tuberculosis among children of Asian ethnic origin born in England. DESIGN--This was a matched case-control study. SETTING--Cases were selected from notifications of tuberculosis and controls were selected from child health or school health records in 14 English health districts. PARTICIPANTS--111 cases of childhood tuberculosis with Asian names were selected. For each case there were five controls with Asian names, matched for age, sex and district of birth. MEASUREMENTS AND MAIN RESULTS--Child health or school health records were searched to determine the proportions of cases and controls who had been vaccinated with BCG. Overall, BCG vaccination given in the first year of life was estimated to confer 49% protection against tuberculosis with 95% confidence interval 14-62%. CONCLUSIONS--BCG vaccination in infancy was found to be associated with a lower protective efficacy than has been found for the secondary school age BCG programme (80%) but nevertheless the protection is substantial and, in the United Kingdom, BCG vaccination of infants considered to be at relatively higher risk of tuberculosis is likely to reduce the incidence of childhood tuberculosis.